SLFN11 expression in advanced prostate cancer and response to platinum-based chemotherapy - Conteduca, Vincenza (Mol Cancer Ther, 2020)
Expression of the DNA/RNA helicase schlafen family member 11 (SLFN11) has been identified as a sensitizer of tumor cells to DNA damaging agents including platinum chemotherapy. We assessed the impact of SLFN11 expression on response to platinum chemotherapy and outcomes in patients with metastatic castration-resistant prostate cancer (CRPC). Tumor expression of SLFN11 was assessed in 41 CRPC patients treated with platinum chemotherapy by RNAseq of metastatic biopsy tissue (n=27) and/or immunofluorescence in circulating tumor cells (CTCs) (n=20). Cox-regression and Kaplan-Meier methods were used to evaluate the association of SLFN11 expression with radiographic progression-free survival (rPFS) and overall survival (OS). Multivariate analysis included tumor histology (ie., adenocarcinoma or neuroendocrine) and the presence or absence of DNA repair aberrations. Patient-derived-organoids with SLFN11 expression and after knockout by CRISPR-Cas9 were treated with platinum and assessed for changes in dose response. Patients were treated with platinum-combination (N=38) or platinum-monotherapy (N=3). Median lines of prior therapy for CRPC was two. Median OS was 8.7 months. Overexpression of SLFN11 in metastatic tumors by RNA-Seq was associated with longer rPFS compared to those without overexpression (6.9 versus 2.8 months, HR=3.72, 95% CI 1.56–8.87, p<0.001); similar results were observed for patients with SLFN11-positive versus SLFN11-negative CTCs (rPFS 6.0 versus 2.2 months, HR=4.02, 95% CI 0.77–20.86, p=0.002). A prostate specific antigen (PSA) decline of ≥50% was observed in all patients with SLFN11 overexpression. No association was observed between SLFN11 expression and OS. On multivariable analysis, SLFN11 was an independent factor associated with rPFS on platinum therapy. Platinum response of organoids-expressing-SLFN11 was reduced after SLFN11 knockout. Our data suggest that SLFN11 expression might identify CRPC patients with a better response to platinum-chemotherapy independent of histology or other genomic alterations. Additional studies, also in the context of PARP inhibitors, are warranted.